Pentingnya Filterisasi Konten Dewasa pada Perkembangan Sosial Emosional Anak Sekolah Dasar - Ismatun Nisak; Isnatul Mukarromah; Luthfiyah Mesi Aditama; Muhammad Nofan Zulfahmi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to provide information and insight into the importance of filtering adult content in the social-emotional development of elementary school children. In today's digital era, technological advances make it easy to access information through various devices such as gadgets. This shows both positive and negative impacts on education, especially if there is no filtering, so children are free to search for information such as adult content that can affect their social emotional development. This study uses a qualitative approach to explain the importance of adult content filtering in the social-emotional development of elementary school children. Data is collected through a literature review that provides a framework or concept to analyze the topic or problem under study. This research includes independent variables and dependent variables. By using a qualitative approach, this research is expected to provide comprehensive facts about the importance of adult content filtering in the social-emotional development of elementary school children. The benefits of this research can provide additional insight for readers regarding the importance of adult content filtering in the social emotional development of elementary school children.